Convergence in carnivorous pitcher plants reveals a mechanism for composite trait evolution - Chomicki, G; Burin, G; Busta, L; Gozdzik, J; Jetter, R; Mortimer, B; Bauer, U (American Association for the Advancement of Science, 2024)
Composite traits involve multiple components that, only when combined, gain a new synergistic function. Thus, how they evolve remains a puzzle. We combined field experiments, microscopy, chemical analyses, and laser Doppler vibrometry with comparative phylogenetic analyses to show that two carnivorous Nepenthes pitcher plant species independently evolved similar adaptations in three distinct traits to acquire a new, composite trapping mechanism. Comparative analyses suggest that this new trait arose convergently through “spontaneous coincidence” of the required trait combination, rather than directional selection in the component traits. Our results indicate a plausible mechanism for composite trait evolution and highlight the importance of stochastic phenotypic variation as a facilitator of evolutionary novelty.